2013
DOI: 10.1038/srep02801
|View full text |Cite
|
Sign up to set email alerts
|

Atomic structure of titania nanosheet with vacancies

Abstract: Titania nanosheets are two-dimensional single crystallites of titanium oxide with a thickness of one titanium or two oxygen atoms, and they show attractive material properties, such as photocatalytic reactions. Since a titania (Ti0.87O2) nanosheet is synthesized by the delamination of a parent layered K0.8Ti1.73Li0.27O4 crystal using a soft chemical procedure, substantial Ti vacancies are expected to be included and affect the material properties. The atomic arrangement of a titania nanosheet with vacancies ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 24 publications
3
58
0
Order By: Relevance
“…The defect formation energy E d for the TiO 2 V model can be estimated by subtracting the energy per formula unit of the Perfect model from that of the TiO 2 V model. The value of E d was obtained to be 3.6 eV, which confirms that the Perfect model is more stable than the TiO 2 V model, though Ti vacancies are introduced in TNSs due to the synthesis method as observed in the TEM experiments [5]. The comparison of the energetic stability between the TiV-H and TiO 2 V models is also possible by calculating the energy gain or loss of the reaction, in which the TiO 2 V model reacts with two H 2 O molecules to form the TiV-H model.…”
Section: A Energetic Stabilitysupporting
confidence: 59%
See 4 more Smart Citations
“…The defect formation energy E d for the TiO 2 V model can be estimated by subtracting the energy per formula unit of the Perfect model from that of the TiO 2 V model. The value of E d was obtained to be 3.6 eV, which confirms that the Perfect model is more stable than the TiO 2 V model, though Ti vacancies are introduced in TNSs due to the synthesis method as observed in the TEM experiments [5]. The comparison of the energetic stability between the TiV-H and TiO 2 V models is also possible by calculating the energy gain or loss of the reaction, in which the TiO 2 V model reacts with two H 2 O molecules to form the TiV-H model.…”
Section: A Energetic Stabilitysupporting
confidence: 59%
“…We found that this reaction has the energy gain of 3.0 eV, which indicates that the TiV-H model is more stable than the TiO 2 V model. As explained in Section II.B, the TiO 2 V model seems to be consistent with the observation of the TEM experiments [5]. In our calculations, we did not consider the energy barriers for the reactions, which may be important to discuss which structure actually appears, and will be studied in our future work.…”
Section: A Energetic Stabilitysupporting
confidence: 56%
See 3 more Smart Citations